A Study of the Strategies of Foreignization and Domestication in Two Persian Translation Versions of Lewiss Caroll's Alice in Wonderland - Fatehi Rad, Neda; Fatehi Marj, Zahra (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2020)
The present study has investigated the translation of cultural translation strategies in an English book as a source text (ST), and its two Persian translations as target texts (TTs). The corpus consists of Lewiss Caroll's "Alice in wonderland" along with two Persian translations by Pirzad (1379) and Honarmandi (1350) as TTs. The data of this study were collected and evaluated based on Venuti's model. This research aimed at investigating the strategies used by translators in rendering the domestication and foreignization. Also, highlighting the frequency of each strategy and identifying the shortcomings of the Persian translations with regard to cultural translation strategies were the other objectives of it.Data were collected by the researcher and were processed through SPSS software. To this end, frequency, percentages, and mean are represented by tables and diagrams. The results of this study indicated that there was a significant difference between the frequencies of the cultural translation strategies. That is to say, "equivalence" was the most frequent one, but the strategies of foreignization have been used very rarely. In the other words, the domestication strategies applied noticeably more than foreignization strategies.